Experimental study on strain accumulation characteristics of saturated remolded loess under pure rotation of the principal stress axis - Wang, Sui; Zhong, Zuliang; Chen, Bin; Wu, Bo; Zhang, Dongyu; Ni, Fuxing (Frontiers in Ecology and Evolution, 2023)
The study conducted pure rotation test of 720° for saturated remolded Q2 loess under the principal stress axis (PSA) rotation when deviatoric stress and intermediate principal stress ratio are different, as well as paid attention to examining the changes of strain accumulation and pore pressure of such loess. According to the test, as the PSA rotates continuously, the pore water pressure exhibited by saturated remolded loess presents a normal cyclic accumulation elevation, and under the same deviatoric stress condition, the pore water pressure accumulation trend of different principal stress ratios is the same, however, the magnitude is different. The increment of pore water pressure becomes smaller as the number of cycles increases. When deviatoric stress level is low, the material hardening is in a cyclic stable state, the strain component remains stable with the continuous rotation of the PSA, and the strain path area is reduced, together with a stable final size. In case of higher deviatoric stress, the material strength cycle becomes weaker, the strain component accumulates slowly as the PSA (the spiral line of the strain path) continuously rotates in the γzθ-(εz-εθ) plane, and gradually expands until failure. The increased intermediate principal stress is accompanied by accelerated strain development speed and advanced failure.